(untitled) (Computer systems and information technologies, 2022)
The paper presents a state-of-art of the methods for cyberattacks detection in the computer networks. The main accent was made on the concept of the resilience for the IT infrastructure. The concept of cyber resilience in the terms of cybersecurity was presented. The survey includes the set of approaches devoted to the problem of construction resilient infrastructures. All investigated approaches are aimed to construct and maintain infrastructure’s resilience for cyberattacks resistance. Mentioned techniques and frameworks keep the main principles to assure resilience. To do this there exists some requirements to construct such infrastructure: IT infrastructure has to include the set ready to use measures of preparation concerning the possible cyber threats; it must include the set of special measures for the protection, as well as for cyberattacks detection; important issue and required is the possibility to respond the attack and to be able to absorb the negative attacks’ impact; IT infrastructure must be as adaptive as it is possible, because today the dynamic of the attacks mutation is very high; IT infrastructure must be recoverable after the attacks were performed. In addition, the state-of-art found out that known approaches have domain-specific usage and it is important to develop new approaches and frameworks for the cyberattacks detection in the computer networks as a means of resilient IT-infrastructure construction.